(untitled) (Acta Scientiarum. Agronomy, 2017)
Micropropagation is an important tool for the multiplication of native Cerrado species. However, understanding the responses of these species under in vitro culture conditions is still incomplete. Thus, the present study aimed to analyze the growth, anatomical behavior and physiology of Pouteria gardneriana cultivated in vitro under photoautotrophic conditions. Nodal segments were cultured at photosynthetic photon flux densities (PPFD) of 75, 100 and 150 µmol m-2 s-1 in culture medium MS 50% solidified with 3.5 g L-1 of agar and 2.0 g L-1 of activated charcoal, in the absence and presence of 30 g L-1 of sucrose. After 60 days of in vitro culture, the P. gardneriana plantlets only regenerated when sucrose was present in the culture medium. Higher fresh and dry weights, higher palisade parenchyma thickness and larger stomatal polar and equatorial diameters were observed in the plantlets cultured at PPFD 150 µmol m-2 s-1. The PPFD difference used in the present study was sufficient to provide additional understanding of the behavior of this species in vitro.